Etiology Analysis and Diagnosis and Treatment Strategy of Traumatic Brain Injury Complicated With Hyponatremia - Zhang, Jianhua; Dong, Wensheng; Dou, Xianghong; Wang, Jinjin; Yin, Peng; Shi, Hui (Frontiers in Surgery, 2022)
Objective: To explore the etiology and diagnosis and treatment strategy of traumatic brain injury complicated with hyponatremia. Methods: The clinical data of 90 patients with traumatic brain injury admitted to our hospital from 2019 to 2020 were retrospectively analyzed to dissect the etiology. Of the 90 cases included, 50 cases diagnosed with hyponatremia were identified as the research objects and assigned to the control group receiving conventional treatment and the experimental group given continuous renal replacement therapy according to the order of admission. The hemodynamic indexes, death rate, and serum neuron-specific enolase (NSE) indexes of the two groups were compared. The Glasgow coma scale (GCS) was used to assess the degree of coma before and after the treatment in the two groups, and the acute physiology and chronic health evaluation scoring system (APACHE II) to evaluate the patient's disease condition. Results: The etiology of traumatic brain injury complicated with hyponatremia is related to the degree of brain injury, ventricular hemorrhage, cerebral edema, and skull base fracture (P<0.05). After the treatment, the hemodynamic indexes, APACHE II scores, death rate, and NSE levels of the experimental group were significantly lower than those of the control group (P＜0.001); The experimental group yielded remarkably higher GAC scores as compared to the control group (P<0.001). Conclusion: The degree of brain injury, ventricular hemorrhage, cerebral edema, and skull base fracture were considered the main factors for traumatic brain injury complicated with hyponatremia. Continuous renal replacement therapy can effectively improve the clinical indicators of the patients with a promising curative effect, which merits promotion and application.